Guide to training opportunities for industrial development: Seventeenth issue - United Nations Industrial Development Organization (Austria United Nations Industria Development Organization, 1989)
This compilation of industrial training opportunities for personnel from developing countries is the seventeenth edition of a UNIDO publication that first appeared in 1972. It is based on a questionnaire soliciting information about training facilities, sent to Governments, organizations, institutions and other bodies concerned with industrial training
osc 04/03/2019
Loans
Keywords: Training; Industrial organization